Decision‐making in home care package spending. (18th August 2020) - Rowland, Diane; Joyce, Catherine M.
Abstract: Objective: To understand the motivations and drivers of spending decisions made by home care package recipients, in the context of high levels of unspent funds. Methods: Qualitative study using 30 semi‐structured interviews with 38 home care package clients and/or client representatives in rural and urban Victoria conducted between December 2018 and March 2019. Interview transcripts were analysed to determine themes. Results: Spending decisions were influenced by assessment and entry experiences, knowledge and understanding of package funds, availability and acceptability of services, and attitudes to spending. Conclusion: Clients need confidence in their individual funds and their use in order to maximise the potential benefits. Clear, consistent communication at all stages, and additional supports to build consumer capability, will enable clients to better understand packages and their application. This in turn will optimise the capacity of home care package recipients to maximise their health and well‐being.